Social differences in smoking and snuff use among Norwegian adolescents: A population based survey - Hovengen Ragnhild; Stigum Hein; Grotvedt Liv; Graff-Iversen Sidsel (BMC, 2008)
Abstract Background A change in pattern of tobacco use has been observed in the last decade in Norway. Snuff use and occasional smoking have to some degree replaced daily smoking among adolescents and young adults. Daily smoking is known to be negatively associated with social background factors, but little is known about these associations for other types of tobacco use. Our aim was to study different types of tobacco use among adolescents according to gender, educational ambitions, family background factors, and urbanization. Methods Cross-sectional, school-based study with 15 931 participants and response-rate 87%, conducted among 15 and 16 year olds during 2000-2004. Results More girls (33.8%) than boys (26.4%) were daily or occasional smokers, while more boys (21.4%) than girls (3.5%) were daily or occasional snuff users. Daily smoking was more common among adolescents planning vocational education, with single parents or poor family economy. Occasional smoking and snuff use (daily or occasionally) showed a similar, but less pronounced pattern regarding education and single parent families. Adolescents with parents from foreign countries were less likely to use tobacco. One exception was boys with parents from Muslim majority countries who had an increased risk of daily smoking. A typical combination user of both tobacco types was a Norwegian boy with divorced parents and ambitions to complete vocational studies or only one year of upper secondary school. Conclusion Tobacco use in adolescents is mainly associated with low educational ambitions and less affluent self-reported family economy. Adolescents with divorced parents use more tobacco than those living with both parents. Public health initiatives to avoid or reduce tobacco use should mainly target adolescents in vocational studies and those leaving school early.